Effects of direct-fed microbials on productive performance, qualitative traits of eggs, blood biochemicals and ileal microflora of laying hens fed wheat-soybean-based diet - Mostafaie , Zahra; Torki , Mehran; Torki , Mehran; Chaghamirza , Kianosh; Sharifi , Rouhallah (Journal of Poultry Sciences and Avian Diseases, 2024)
This study investigated the effects of direct-fed microbes on qualitative traits of eggs and productive performance, ileal and cecal microflora, and pH of hens fed wheat-based diets from 60 to 68 wk of age. The total number of 240 Hy-Line W-36 laying hens were randomly distributed between 40 cages, and the five experimental diets including (A) corn-soybean meal-based control diet, (B) wheat-based diet with no microbial additive, (C) wheat-based diet supplemented with Bacillus velezensis, (D) wheat-based diet supplemented with S. cerevisiae and (E) wheat-based diet supplemented with B. velezensis + S. cerevisiae were assigned to hens with eight replicate cages per diet and six hens per each replicate. Increased egg weight and production (EP), feed intake (FI), improved feed conversion ratio (FCR), and decreased pH of ileum and caecum were observed in layers fed the diet included B. velezensis + S. cerevisiae (P<0.05). Improved intestinal morphology characteristics were observed in hens fed the microbe-added diets (P<0.05). Increased plasma protein, albumen, and HDL in hens fed microbe-added diets (P<0.05). Adding B. velezensis + S. cerevisiae to the diet modulated the ileal and caecal microflora composition by decreasing the numbers of Salmonella and increasing the numbers of Lactobacilli. Based on the results of the current study, it can be concluded that adding B. velezensis + S. cerevisiae to the wheat-based diet improves performance and intestinal morphology characteristics of laying hens, decreases plasma levels of cholesterol, triglyceride, and LDL, and the intestinal pH and number of Salmonella.